2019
DOI: 10.1016/j.radonc.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy using proton beams for unresectable locally advanced pancreatic cancer

Abstract: Background and purpose: We investigated clinical outcomes of proton beam concurrent chemoradiotherapy (CCRT) for unresectable, locally advanced pancreatic cancer (LAPC) patients. Materials and methods: Records from 42 unresectable LAPC patients (21 male and 21 female, 39-83 years old) with IIB/III clinical staging of 1/41 treated by proton beam CCRT were retrospectively reviewed. Twelve patients received a conventional 50 Gray equivalents (GyE) in 25 fractions protocol and 30 others received a higher dose prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 45 publications
4
49
0
1
Order By: Relevance
“…Maemura, et al's [71] comparative PT study of 25 patients (10 undergoing PT and 15 undergoing hyper-fractionated XRT) only had two patients develop grade ≥ 2 gastric ulcers, still appearing advantageous compared to XRT and C-ion regarding high grade haematological toxicity when gemcitabine was employed. In fact, Hiroshima, et al's [45] PT trial reported all grade ≥ 3 and 4 events were haematologic and correlated with full-dose gemcitabine and/or speculated as high doses to the spleen (as previously described in XRT studies [72,73]).…”
Section: Gaps In Particle Therapy For Pancreatic Cancermentioning
confidence: 68%
See 4 more Smart Citations
“…Maemura, et al's [71] comparative PT study of 25 patients (10 undergoing PT and 15 undergoing hyper-fractionated XRT) only had two patients develop grade ≥ 2 gastric ulcers, still appearing advantageous compared to XRT and C-ion regarding high grade haematological toxicity when gemcitabine was employed. In fact, Hiroshima, et al's [45] PT trial reported all grade ≥ 3 and 4 events were haematologic and correlated with full-dose gemcitabine and/or speculated as high doses to the spleen (as previously described in XRT studies [72,73]).…”
Section: Gaps In Particle Therapy For Pancreatic Cancermentioning
confidence: 68%
“…Established as a broad ranging anti-tumour treatment gemcitabine is the most widely recommended chemotherapy agent to reduce this risk of distant metastasis and regional recurrence, the major mode of LAPC treatment failure. However, administration of gemcitabine has been linked to a higher incidence of grade ≥ 3 haematological toxicities across chemoradiation trials (Tables 2-4 [45] PT trial reported all grade ≥ 3 and 4 events were haematologic and correlated with full-dose gemcitabine and/or speculated as high doses to the spleen (as previously described in XRT studies [72,73]). Developments in particle therapy have marginally improved MST, LC and OS in recent years, whilst marginally reducing the incidence and grade of GI toxicities compared to XRT (Figures 2 and 3).…”
Section: Gaps In Particle Therapy For Pancreatic Cancermentioning
confidence: 72%
See 3 more Smart Citations